Inventario de rodeos montubios como atractivo turístico de la Provincia de Los Ríos - Campi Bravo, Humberto Yael (2022)
The main purpose of the case study is to analyze the inventory of montuvio rodeos as a tourist attraction in the province of Los Ríos. For this, a survey of 200 randomly chosen residents of the province was implemented in order to know their opinions on cultural tourism. tourist inventories and innate tourist activities of different localities, it is important to point out that in order to achieve the study, the inductive research method was applied, where it was possible to reach general conclusions of the planning, promotion and realization of the montuvio rodeos; At the same time, the deductive method allowed obtaining specific information on the situations that arise in the execution of that tourist activity, in addition, the analytical method, which helps to establish an exhaustive analysis of the montuvio rodeos and the management they carry out the authorities in the elaboration of an appropriate tourist inventory. Additionally, the types of quantitative and qualitative research that contributed to obtaining numerical data and their respective interpretation were applied. Thus, it was possible to identify the lack of an adequate tourist inventory and the lack of knowledge that people have about the tourist potential of the montuvio rodeos.